JIGSAW: METODE PENINGKATAN DISKUSI DALAM MATA PELAJARAN IPS - Salam, Aldi; Hanifah, Heni; Milandi, Siska Destia; Ratnawati, Etty (CV Kalimasada Group, 2024)
This study examines Jigsaw's efforts to increase student engagement in class discussions in Social Studies (IPS). The data collection method was carried out using the literature review technique, which involved analyzing various journals and articles related to the application of the Jigsaw method in the context of learning. This study highlights how the Jigsaw method is able to create an interactive and collaborative learning environment, so that students feel more involved in the discussion process. Findings from the literature show that this method not only increases student participation but also encourages better mastery of the material and the development of social skills. In addition, the results of the analysis show a positive relationship between the use of the Jigsaw method and increased student learning motivation. This study provides recommendations for educators to apply the Jigsaw method as an effective strategy to increase student engagement in class discussions in IPS.